Human perception of visual stimuli modulated by direction of linear polarization - Misson, Gary P.; Timmerman, Brenda H.; Bryanston-Cross, Peter J. (Vision research (Oxford), 2015)
[Display omitted] •Human polarized light perception extends beyond Haidinger’s phenomenon (HP).•The radial analyser model predicts the polarization-induced percepts.•Humans are sensitive to static and kinetic patterned polarization stimuli.•Unlike HP, static patterned polarization stimuli are easily perceived.•Any pattern can be encoded into identifiable polarization stimuli. This study explores both theoretically and experimentally the human perception of polarized light beyond that currently established. The radial analyser theory of Haidinger’s phenomenon (HP) is used to predict the effect of observing visual stimuli comprising patterned zones characterized by orthogonal planes of linear polarization (linear polarization direction fields, LPD-fields). Any pattern can be represented as an LPD-field including optotypes and geometric forms. Simulated percepts differ from the original patterns although edges are mostly preserved. In edge-rich images a cross of attenuating contrast spanning the field of view is predicted. The mathematical model is verified experimentally using a liquid crystal display (LCD)-based polarization modulator imaged through a tangential (azimuthal) analyser with properties complementary to a radial analyser. The LCD device is then used in vivo to elicit perceptual responses in human subjects. Normal humans are found to readily detect spatially and temporally modulated isoluminant spatially-isochromatic, highly polarized LPD stimuli. Most subjects match the stimuli to corresponding images of theoretically predicted percepts. In particular edge perception and the presence of the contrast cross was confirmed. Unlike HP, static patterned LPD stimuli are perceived without difficulty. The simplest manifestation of human polarization perception is HP which is the fundamental element of an open set of stimulus-dependent percepts. This study demonstrates that humans have the ability to perceive and identify visual pattern stimuli defined solely by polarization state modulation.